2013
DOI: 10.2737/rmrs-rp-103
|View full text |Cite
|
Sign up to set email alerts
|

Fuel treatments and fire severity: A meta-analysis

Abstract: We employed meta-analysis and information theory to synthesize findings reported in the literature on the effects of fuel treatments on subsequent fire intensity and severity. Data were compiled from 19 publications that reported observed fire responses from 62 treated versus untreated contrasts. Effect sizes varied widely and the most informative grouping of studies distinguished three vegetation types and three types of fuel treatment. The resultant meta-analytic model is highly significant (p<0.001) and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 8 publications
(12 reference statements)
5
66
1
Order By: Relevance
“…Fuel treatment effectiveness, including PB, varies with vegetation and treatment type [11]. PB is stand replacing in open, single-layered vegetation types (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Fuel treatment effectiveness, including PB, varies with vegetation and treatment type [11]. PB is stand replacing in open, single-layered vegetation types (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…When untreated forest burns under severe fire weather conditions, fire severity is generally high (Martinson and Omi 2013;Safford et al 2012;Stevens et al 2014). When treated forest burns in a wildfire, there is generally less effect on the forest overstory than in untreated forest, suggesting that treatments can increase forest resilience to future disturbance.…”
Section: Effects On Vegetationmentioning
confidence: 99%
“…In YPMC forests, fuel treatments have proven effective at reducing fire severity and tree mortality, restoring forest structure and protecting human infrastructure and lives across the western United States (Martinson and Omi 2013;Safford et al 2009;Safford et al 2012). They also hold promise as sources of forest biomass, which can be used to produce a variety of timber and nontimber forest products as well as energy through biomass burning (Evans and Finkral 2009).…”
mentioning
confidence: 99%
“…They concluded that with few exceptions, fire severity measures, such as bole char height, scorch and torch height, scorch and torch percentage, and tree mortality were much lower in forest stands treated for fuels than in neighboring untreated stands. Martinson et al [9] developed a meta-analytic model to synthesize results from 19 publications that reported observed fire responses from 62 treated versus untreated contrasts in confer forests. Their final model was highly significant (p < 0.001) and explained 78% of the variability in reported observations of fuel treatment effectiveness, indicating that the overall mean effect of fuel treatments on fire intensity and severity is large and significant.…”
Section: Potential Benefits Of Fuel Reduction Treatments In Forested mentioning
confidence: 99%
“…Importance or objective (3, 5, 7) (9, 10, 10) (7,9,10) In the fourth step, fuzzy TOPSIS is applied to the triangular fuzzy numbers in Table 4 to rank the three FRTs for each climate future. The ranking for the constructed example is shown in Table 5.…”
Section: Constructed Example For Public Landscape (Case 2)mentioning
confidence: 99%